Chemical Validation of Mycobacterium tuberculosis Phosphopantetheine Adenylyltransferase Using Fragment Linking and CRISPR Interference. Issue 17 (13th March 2023) - El Bakali, Jamal; Blaszczyk, Michal; Evans, Joanna C.; Boland, Jennifer A.; McCarthy, William J.; Fathoni, Imam; Dias, Marcio V. B.; Johnson, Eachan O.; Coyne, Anthony G.; Mizrahi, Valerie; Blundell, Tom L.; Abell, Chris; et al.
Abstract: The coenzyme A (CoA) biosynthesis pathway has attracted attention as a potential target for much‐needed novel antimicrobial drugs, including for the treatment of tuberculosis (TB), the lethal disease caused by Mycobacterium tuberculosis ( Mtb ). Seeking to identify inhibitors of Mtb phosphopantetheine adenylyltransferase ( Mtb PPAT), the enzyme that catalyses the penultimate step in CoA biosynthesis, we performed a fragment screen. In doing so, we discovered three series of fragments that occupy distinct regions of the Mtb PPAT active site, presenting a unique opportunity for fragment linking. Here we show how, guided by X‐ray crystal structures, we could link weakly‐binding fragments to produce an active site binder with a K D <20 μM and on‐target anti‐ Mtb activity, as demonstrated using CRISPR interference. This study represents a big step toward validating Mtb PPAT as a potential drug target and designing a Mtb PPAT‐targeting anti‐TB drug. Abstract : A fragment screen yielded three series of Mycobacterium tuberculosis phosphopantetheinyl adenylyltransferase ( Mtb PPAT) ligands that bind to distinct regions within the active site. This presented a unique opportunity for fragment linking that was exploited for the design of higher affinity ligands, shown, using CRISPR interference, to possess on‐target antimycobacterial activity.